Sadar Pajak Bagi Wajib Pajak Pemula - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to explore the meaning of tax awareness among novice taxpayers from a qualitative perspective. Tax awareness is often narrowly understood as technical knowledge or compliance with tax regulations, whereas for novice taxpayers it is shaped through social experiences, early interactions with the tax system, and environmental influences. This research adopts a qualitative descriptive-interpretative approach to capture how novice taxpayers understand and experience tax awareness during their initial engagement with taxation. Data were collected through in-depth semi-structured interviews with novice taxpayers and supported by limited observation and documentation. The findings reveal that tax awareness among novice taxpayers is predominantly normative, reflecting a sense of obligation as citizens rather than comprehensive technical understanding. Early experiences with tax administration and narratives circulating in the social environment significantly influence how tax awareness is formed. Furthermore, the study finds a gap between tax awareness and tax compliance, indicating that awareness does not automatically translate into consistent compliance, particularly when the tax system is perceived as complex and unfriendly. This study highlights the need for more empathetic and educational approaches in fostering sustainable tax awareness among novice taxpayers